Health Related Quality of Life of Patients with Rheumatoid Arthritis Attending in a Rheumatic Center, Lalitpur - Budhathoki, Babita; Onta, Mandira; Singh, Ajanta; Adhikai, Bibhav (Medical Journal of Shree Birendra Hospital, 2022)
Introduction: Rheumatoid Arthritis is a systemic autoimmune disorder, whose major distinctive feature is chronic, symmetrical, and erosive inflammation of the synovial tissue of joints which has a significant impact on patients’ physical, mental and social well-being, resulting in low health-related quality of life. The main objective of the study was to find out the health-related quality of life of patients with rheumatoid arthritis in a selected rheumatic Centre, Lalitpur. Method: A Descriptive cross-sectional design was adopted among 115 rheumatoid arthritis patients through non-probability purposive sampling. Data was collected through face to face interview taking written informed consent. Data was collected from 2nd September to 28th September 2018. Data were analyzed through descriptive and inferential statistics using SPSS version 16. Result: In this study, the mean score of the overall health-related quality of life was 55.84±13.43. The mean physical component score was 55.96±13.61 and the mental component score was 45.42±13.84. Regarding association with the physical quality of life, age (p=0.008) and type of family (p=0.04) which were significantly associated. Regarding association with mental quality of life, age (p=0.02), marital status (p=0.03) and BMI (p= 0.001) which were significantly associated with mental quality of life. Conclusion: The overall health-related quality of life of patients with Rheumatoid Arthritis was average whereas mental health domain score was below average. Thus, both physical and mental domain of health-related quality of life should be considered by the concerned authority.